P0291MYELOMA CAST NEPHROPATHY, LIGHT CHAIN DEPOSITION DISEASE, AND BOTH IN PATIENTS WITH NEWLY DIAGNOSED MULTIPLE MYELOMA. (6th June 2020) - Lin, Zishan; Yu, Xiaojuan; Wang, Suxia; Zhou, Fude; Zhao, Minghui
Abstract: Background and Aims: The pathological patterns of myeloma-related kidney disease are various, in which myeloma cast nephropathy (MCN) and light chain deposition disease (LCDD) are two of the main patterns. Of note, in patients with multiple myeloma (MM), these two patterns of pathology can occur at the same time. However, there are limited data available showing the difference of clinical characteristics and outcomes among newly diagnosed MM patients with these three patterns of pathology. In this study, we retrospectively reviewed 42 newly diagnosed MM patients with renal biopsy-proven pure MCN, pure LCDD or MCN with coexistent LCDD in Peking University First Hospital, to describe the clinical characteristics, treatment, and outcomes, in order to help define the spectrum of prognostic profiles. Method: All the native renal biopsies between September 1999 and October 2019 at Peking University First Hospital were retrospectively restudied. A total of 42 newly diagnosed MM patients with pure MCN (n=24), pure LCDD (n=8) and MCN with coexistent LCDD (n=10) were enrolled. The clinical features, as well as prognostic risk factors for renal survival and overall survival were retrospectively investigated. Results: The 42 parents consisted of 26 men and 16 women with a mean age of 53.2±10.9 years. There was no significant difference in age and gender among the 3 groups. Patients with pure LCDD had significantly higher hemoglobin levels, a higher percentage of albumin in urine protein, a lower incidence of progressing to ESRD and more likely to present with AKD than patients with pure MCN or with MCN+LCDD. Patients with pure LCDD had significantly higher serum creatinine levels, a lower eGFR, a lower incidence of death and more likely to present with nephrotic syndrome than patients with pure MCN, but no different than patients with MCN+LCDD. No significant difference between pure MCN and MCN+LCDD. Median renal survival in LCDD group (not reached) was significantly higher compared to MCN (11 months, p = 0.002) group and MCN+LCDD group (1months, p = 0.012, Figure 1). Median overall survival in LCDD group (not reached) was significantly higher compared to MCN (39 months, p = 0.014) group, but had no difference with MCN+LCDD group (not reached, p = 0.199, Figure 2). According to the multivariate analysis, the independent predictors of renal survival were hemoglobin (HR: 0.957, 95% CI: 0.922-0.994; p = 0.022) and eGFR (HR: 0.940, 95% CI: 0.880-0.995; p = 0.034), the independent predictors of overall survival were hemoglobin (HR: 0.943, 95% CI: 0.895-0.993; p = 0.025) and pure MCN (HR: 7.597, 95% CI: 1.171-49.272; p = 0.034). Conclusion: Patients with MCN+LCDD presented similar in clinical characteristics to patients with pure MCN and both suffer from more serious and more urgent renal damage than patients with pure LCDD. However, the overall survival in patients with MCN+LCDD was similar to patients with pure LCDD while the renal survival was worse. Hemoglobin and eGFR were independent predictors of renal survival and hemoglobin and pure MCN were independent predictors of overall survival.